2011
DOI: 10.2147/ijn.s16973
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear entry of hyperbranched polylysine nanoparticles into cochlear cells

Abstract: Background: Gene therapy is a potentially effective therapeutic modality for treating sensorineural hearing loss. Nonviral gene delivery vectors are expected to become extremely safe and convenient, and nanoparticles are the most promising types of vectors. However, infrequent nuclear localization in the cochlear cells limits their application for gene therapy. This study aimed to investigate the potential nuclear entry of hyperbranched polylysine nanoparticles (HPNPs) for gene delivery to cochlea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 41 publications
1
24
0
2
Order By: Relevance
“…The accumulation of hyaluronic acid might contribute to an increased permeability and microcirculation inflammation in renal ischemic reperfusion injury [20]. Previous studies demonstrated that the rodent inner ear was an excellent organ for the evaluation of nanoparticle biocompatibility due to its sophisticated barrier system [21][22][23], and AgNPs were capable of disrupting the blood-inner ear barriers, as indicated by magnetic resonance imaging (our unpublished data). Therefore, the current research was designed to verify the hypothesis that an accumulation of glycosaminoglycan associated with the up-regulation of hyaluronic acid in the basement membrane is involved in the kidney and cochlea impairments following exposure to AgNPs.…”
Section: Introductionmentioning
confidence: 87%
“…The accumulation of hyaluronic acid might contribute to an increased permeability and microcirculation inflammation in renal ischemic reperfusion injury [20]. Previous studies demonstrated that the rodent inner ear was an excellent organ for the evaluation of nanoparticle biocompatibility due to its sophisticated barrier system [21][22][23], and AgNPs were capable of disrupting the blood-inner ear barriers, as indicated by magnetic resonance imaging (our unpublished data). Therefore, the current research was designed to verify the hypothesis that an accumulation of glycosaminoglycan associated with the up-regulation of hyaluronic acid in the basement membrane is involved in the kidney and cochlea impairments following exposure to AgNPs.…”
Section: Introductionmentioning
confidence: 87%
“…20 L929, a normal cell line, has been widely used in a series of studies including drug delivery to the inner ear. 21,22 As shown in Figure 1A, the viability of L929 cells remained high after being treated with the four types of NPs at various concentrations, even up to 25 mg/mL (the original NPs suspension), suggesting that PLGA-based …”
Section: Resultsmentioning
confidence: 94%
“…(42) Nuclear entry of polylysine nanoparticles (73 nm hydrodynamic diameter) was also observed in chochlear cells. (42,43) Further confirmatory methods may be required to study this phenomenon.…”
Section: Figmentioning
confidence: 99%